Respuesta :

Answer:

5x-1

Step-by-step explanation:

f(x) = 3x-2

g(x) = 2x+1

(f+g) (x) = 3x-2 + 2x+1

Combine like terms

            = 5x -1

Space

Answer:

C. 5x - 1

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Terms/Coefficients
  • Functions
  • Function Notation

Step-by-step explanation:

Step 1: Define

Identify

f(x) = 3x - 2

g(x) = 2x + 1

(f + g)(x) is f(x) + g(x)

Step 2: Find

  1. Substitute in functions:                                                                                     (f + g)(x) = 3x - 2 + 2x + 1
  2. [Addition] Combine like terms (x):                                                                   (f + g)(x) = 5x - 2 + 1
  3. [Addition] Combine like terms:                                                                        (f + g)(x) = 5x - 1
ACCESS MORE